Pelatihan Manajemen Keuangan Dasar bagi UMKM Perempuan di Kota Medan: Penerapan Pemisahan Keuangan Pribadi dan Usaha - Amilia Hasbullah; Ahmad Hermanto (Lembaga Pengembangan Kinerja Dosen, 2026)
Women micro, small, and medium enterprises (MSMEs) play a strategic role in strengthening both family and community economies; however, they experience to obtain fundamental skill in financial management. One of the main problems is the mixing of personal and business finances, which turn into challenges for entrepreneurs to monitor business performance and to address access financing. This community service activity aims to improve insight of women entrepreneurs in Medan regarding the importance of separating personal and business finances through simple, practice-based training. The activity was conducted in 7 November 2025 in Medan and was attended by 150 women MSME participants from a local entrepreneurship community. The training was held for one day using interactive lectures, group discussions, and hands-on cash recording exercises. The results showed a significant improvement in participants’ understanding of financial separation concepts and their ability to record business transactions. A total of 85% of participants were able to create a simple cash record format and expressed a commitment to applying separate financial practices. This activity contributed to improving the financial literacy of women micro-entrepreneurs and strengthening their managerial capacity toward sustainable business growth.